AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL KUMIS KUCING ( Orthosipon Aristatus )TERHADAP PERTUMBUHAN BAKTERI Staphyloccocus aureus DENGAN MENGGUNAKAN METODE DIFUSI - Aulia Debby Pelu; Cut Bidara Panita Umar; Nadhira Fahreza Patimahu (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
Cat's whiskers leaf plant (Ortosiphon aristatues.) is one of the plants that is efficacious as a medicinal plant. The part of the cat's whiskers leaf plant is used, namely the leaves that contain saponin compounds, flavonoids, alkaloids and tannins. The purpose of this study was to determine the most effective inhibition produced by the ethanol extract of the leaves of the cat's whiskers (Ortosiphon aristatues.) against the growth of Staphyloccocus aureus bacteria. The benefit of this research is to increase knowledge about the antimicrobial potential of ethanol extract of cat whiskers (Ortosiphon arietatus) leaves against the growth of Staphyloccocus aureus bacteria. This research method uses the diffusion method for wells. The sample used was cat whiskers leaf extract with pure strain of Staphyloccocus aureus. Treatment with cat whiskers leaf extract, the results of the test of the inhibitory activity of the cat whiskers leaf extract showed an average difference at a concentration of 65% with a diameter of 22 mm, a concentration of 70% with a diameter of 25 mm, and a concentration of 75% with a diameter of 30 mm. Ethanol extract of cat whiskers leaves with a concentration of 65%, 70%, and 75% effectiveness in inhibiting the growth of Staphylococcus aureus bacteria. Based on observations, it was shown that the ethanolic extract of Kumis Kucing leaves gave the most effective inhibitory concentration at a concentration of 75% against Staphyloccocus aureus bacteria. with a diameter of 30 mm